MARKETING STRATEGY ANALYSYS FOR HOTEL ROOMS INC BTC BANDUNG - Anisa Nur Syabani; Syahbilla Nur Oktora; Syipa Fauziah; Budi Prasetiyo (Media Inovasi Pendidikan dan Publikasi, 2023)
Every tourism company competes to generate large profits by using natural resources and presenting various tourism products. As an industry engaged in the service sector, Room Inc. strives to provide maximum service for its visitors. Each hotel will try to provide added value that is different for each product and service as well as the services provided to its guests. In this study the authors used observation and interview methods. This study aims to produce information that can be useful and complete. Based on the results of research that has been carried out by researchers concluded Rooms Inc BTC Hotel Bandung uses a marketing strategy in its promotion using online and offline media in order to increase sales. Of course online and offline promotions have differences, online sales have higher sales than offline sales. Based on the data and information obtained from interviews and observations, the authors argue that online promotion has a good effect on increasing sales. One of them is promotion on social media, namely Instagram, which works with influencers to increase brand awareness and build interaction with the intended potential consumers, but this must be further enhanced by using influencer approaches and strategies.